Aprendizagem social de jovens rurais em ambientes do Baixo São Francisco sergipano - Gois, Camila Bomfim de (2019)
This thesis had as objective to analyze the experience of young people from rural area and formative network's associations particularly those committed to strengthening social development actions in the hinterlands of Sergipe known as Baixo Sertão Sergipano, attached to the Associação de Produtores de Orgânicos de Ponta de Areia (APOP), Pacatuba-SE (Union of Organic Producers from Ponta de Areia, from Pacatuba -SE). Social learning involves pedagogical actions, but it also concerns, the senses of meanings of their daily action, an individual and collective commitment to the resolution of nowadays socio-environmental issues, within the focus on tomorrow´s repercussions. Thus, it is necessary to consider the disparities experienced by a group of people in the construction and/or strengthening of relationships and interactions between man and environment (economy, politics, education, ecology, culture). The research had a qualitative approach of the ethnographic type, took place through the analysis of semi-structured interviews, field observations, and analysis of documents. Additional tools such as field notes, photographs, conversations, and recordings also supported the construction and validation of data. The results show a social learning process for sustainability in the schooling of young people, and a consequent consolidation of partnerships. Partnerships, intermediaries or outsourcing for the formation of exchange spaces beyond the limits of the Association's headquarters. They also point out that any medium- and long-term and/or long-term development project imposes transformations within the education to achieve its full effectiveness.